Applied epistemology - Lackey, Jennifer (Oxford University Press, 2021)
Leading philosophers bring the tools of contemporary epistemology to bear on some of the most pressing social and political questions facing us as agents in the world today. This volume explores a diverse range of topics as they relate to epistemology under broad themes including injustice, race, feminism, sexual consent, and the internet.
Le texte d' Emmalon Davis, “A Tale of Two Injustices: Epistemic Injustice in Philosophy” a été donné au cours FEM9000.
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; fem9000; histoire et politique; injustice; justice sociale; philosophie; sciences humaines; thématiques; violences; épistémologie; éthique